PROMOTING WOMEN'S ROLE THROUGH MSMEs E-COMMERCE AND DIGITALIZATION OF FINANCIAL REPORTS IN THE FRAMEWORK OF INCREASING PRODUCTIVITY - Yunita, Nur Afni; Nurhasanah; Rany Gesta Putri Rais; Awaliyah, Fitri; Asvia, Meulu (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
The role of women experiences obstacles in mastering digital media, both in the field of marketing and creating digital financial reports, which becomes an obstacle in increasing productivity, therefore the team created training on creating e-commerce and preparing computer-based accounting financial reports. Community Empowerment Services activities are carried out using 4 (four) methods, namely the first method of identification includes theoretical study activities, the second method consists of searching for partners by conducting field observations and interviews regarding problems faced by partners within the scope of e-commerce and digitalization of financial reports. The third method is in the form of partner assistance training in the form of MSMEs E-Commerce and digital financial reports that use accounting computer applications as a means of increasing productivity. Furthermore, in the fourth method, evaluation is carried out so that the training carried out is right on target in accordance with the objectives of Community Empowerment Services activities.